Peranan sokongan pembelajaran dalam keterlibatan murid: Perbezaan gender terhadap pencapaian [The role of learning support in students engagement: gender differences toward achievement] - Mohd Yusoff, Hanita (2017)
Purpose - The study examined the relationship between students engagement and learning supports with students achievement based on gender.It also examined the extent to which the engagement role as a mediator to learning support towards students achievement.Methodology - Cross sectional surveys are used to collect data on students’ engagement at school, learning support and academic achievement.The sample of the study consists of form four boys and girls (16 years old, N = 800) from secondary schools in urban and rural areas in the district of Kuala Selangor.The Student Engagement Scale (Lam et.al 2009) translated into bahasa Melayu by Zalizan et al (2013) is used for data collection.Pearson correlation inference analysis was conducted to determine the relationship between variables. An analysis of the structured equation model (SEM) was carried out to identify the role of involvement as a mediator of teachers’, peers’ and parents’ support towards students’ achievement by gender.Findings - The findings show that there is a significant relationship between the engagement and students’ learning support with academic achievement by gender.It also shows student engagement is an intermediary contribution between learning support towards the achievement of boys and girls.Significance - The result of this study provide a basis to reinforce school’s administration theory on the role of student engagement as an intermediary of learning support towards achievement.These results can be useful for teachers to initiate intervention programs for increasing the quality of learning support- teacher, peer and parent support which could improve academic engagement and outcomes.